Adsorção de polieletrólitos em superfícies opostamente carregadas - Silva, Alexandre Nogueira da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Understanding the interactions between polyelectrolytes and oppositely charged macroíons is important due to the great number of biological processes and technological advances in which they are related. In this context the process known as adsorption is quite important, which led to a series of theoretical, experimental and theoretical-computational studies for his better understanding. On systems with plane geometry the problem has analytical solution, however for spherical and cylindrical geometry this no longer occurs due to the problem of lack of analytical solutions for the electrostatic potential in these geometries. The experiments show that there is a scaling relation between the concentration of ionic species contained in the electrolytic solution in which the polyelectrolyte-macroíon system lies and the surface charge density of the polymer and macroíon. In this study we used the concept of factorization, stemmed on the Supersymmetric Quantum Mechanics, applied to Edwards equation to obtain an approximate analytic solution for the spherical case in an agreement with the experimentally observed

O entendimento das interações entre polieletrólitos e macroíons de carga oposta se faz patente devido aos inúmeros processos biológicos e avanços tecnológicos em que estão relacionados. Nesse contexto o processo conhecido como adsorção apresenta grande importância, o que motivou uma série de estudos teóricos, experimentais e teórico-computacionais para sua melhor compreensão. Em sistemas com geometria plana o problema possui solução analítica, entretanto para as geometrias esférica e cilíndrica isso já não ocorre, devido ao problema da não existência de soluções analíticas para os potencias eletrostáticos nessas geometrias. Os experimentos mostram que existe uma relação de escala entre a concentração de espécies iônicas contidas na solução eletrolítica em que o sistema macroíon-polieletrólito se encontra e a densidade superficial de carga do macroíon e do polímero. Neste trabalho foi utilizado o conceito de fatoração provinda da Mecânica Quântica Supersimétrica aplicado à equação de Edwards de modo a obter para o caso esférico uma solução analítica aproximada que apresente concordância com o observado experimentalmente
Keywords: Físico-química; Adsorção; Quimica de superficie; Supersimetria; Polietrólitos